1975
DOI: 10.1210/jcem-40-3-373
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Δ5-Androstene-3β,17β-diol with Estradiol and Dihydrotestosterone Receptors in Human Myometrial and Mammary Cancer Tissue1

Abstract: Specific receptor binding of estradiol (E-2) and dihydrotestosterone (DHT) was studied in human myometrial tissue and in human mammary cancer tissue. The inhibition of binding for E-2 and DHT by E-2, testosterone (T), DHT, dehydroepiandosterone (DHEA), dehydroepiandrosterone-sulfate (DHEA-S), androstendione (A) and 5-androstene-3beta, 17beta-diol (Adiol) was tested with the use of dextran-coated charcoal separation of bound and free E-2, respectively, and DHT. The percentage of binding inhibition was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

1976
1976
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 0 publications
2
30
0
2
Order By: Relevance
“…In rats, DHEA is metabolised in situ in many tissues mainly to 7 -hydroxy DHEA by the -hydroxylase CYP7B, or to ADIOL, which can also be -hydroxylated, presumably by the same enzyme (Rose et al 2001). In vitro and in vivo data suggest oestrogenor androgen-like effects of DHEA and its metabolites, depending on sex hormone homeostasis (Poortman et al 1975). The present results showed that in pituitary hyperplasia induced by oestrogen, DHEA had several endocrine and metabolic effects, which depended mainly on the endocrine environment.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In rats, DHEA is metabolised in situ in many tissues mainly to 7 -hydroxy DHEA by the -hydroxylase CYP7B, or to ADIOL, which can also be -hydroxylated, presumably by the same enzyme (Rose et al 2001). In vitro and in vivo data suggest oestrogenor androgen-like effects of DHEA and its metabolites, depending on sex hormone homeostasis (Poortman et al 1975). The present results showed that in pituitary hyperplasia induced by oestrogen, DHEA had several endocrine and metabolic effects, which depended mainly on the endocrine environment.…”
Section: Discussionmentioning
confidence: 48%
“…When DES and DHEA were combined, we found that BW loss induced by the oestrogen was slightly reversed. This indicates that DHEA by itself may be acting as a weak oestrogen but in combination with DES it may antagonise its effect by partially displacing DES from oestrogen receptors, directly or via ADIOL (Poortman et al 1975), or it may act as an androgenic compound. In this respect it has also been shown that DHEA produced a significant reduction of BW in unstressed rats, but that it reversed the inhibition of BW gain in stressed rats (Hu et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nafoxidine is a specific and very potent inhibitor of the binding of estradiol to its receptor, but does not inhibit the binding of estradiol to SHBG, albumin or other plasma constituents [9].…”
Section: Specificitymentioning
confidence: 99%
“…As mentioned above, the major metabolites found in rat and monkey brain after systemic administration of DHEAS appear to be DHEA and androstenediol. Although both androgens, the latter has estrogenic properties (Poortman et al, 1975) and COUMATE itself is devoid of such activity (Purohit et al, 1996).…”
Section: Discussionmentioning
confidence: 99%